2021
DOI: 10.1051/0004-6361/202039772
|View full text |Cite
|
Sign up to set email alerts
|

Low-redshift compact star-forming galaxies as analogues of high-redshift star-forming galaxies

Abstract: We compare the relations among various integrated characteristics of ∼25 000 low-redshift (z ≲ 1.0) compact star-forming galaxies (CSFGs) from Data Release 16 (DR16) of the Sloan Digital Sky Survey and of high-redshift (z ≳ 1.5) star-forming galaxies (SFGs) with respect to oxygen abundances, stellar masses M⋆, far-UV absolute magnitudes MFUV, star-formation rates SFR and specific star-formation rates sSFR, Lyman-continuum photon production efficiencies (ξion), UV continuum slopes β, [O III] λ5007/[O II] λ3727 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0
15

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 138 publications
5
46
0
15
Order By: Relevance
“…Nevertheless, we can see that the range of values that our survey covers overlaps with most of the range of the extremely metal poor and strongly star forming samples, in contrast with Yang et al (2017) and Cardamone et al (2009). In addition, we plot as well the typical values for other types of systems, some with strong ionizing spectra: HeII emitters (Pérez-Montero et al 2020) and Lyman α emitters (Matthee et al 2021;Izotov et al 2021). In these cases, their ratios are more similar to ours.…”
Section: Number Density Of Eelgsmentioning
confidence: 77%
See 1 more Smart Citation
“…Nevertheless, we can see that the range of values that our survey covers overlaps with most of the range of the extremely metal poor and strongly star forming samples, in contrast with Yang et al (2017) and Cardamone et al (2009). In addition, we plot as well the typical values for other types of systems, some with strong ionizing spectra: HeII emitters (Pérez-Montero et al 2020) and Lyman α emitters (Matthee et al 2021;Izotov et al 2021). In these cases, their ratios are more similar to ours.…”
Section: Number Density Of Eelgsmentioning
confidence: 77%
“…The error bars represent the maximum and minimum value without outliers, which are plotted as dots (and defined as the values that lie beyond 1.5 times the inter quartilic range). We plot in this figure results from the present work and several samples from the literature (Yang et al 2017;Cardamone et al 2009;Amorín et al 2015;Onodera et al 2020;Hsyu et al 2018;Guseva et al 2017;Pérez-Montero et al 2020;Matthee et al 2021;Izotov et al 2021), as well as the KISS survey (Wegner et al 2003;Gronwall et al 2004;Jangren et al 2005;Salzer et al 2005) and the Hα dots class (Kellar et al 2012;Salzer et al 2020). We have selected the subsample with extremely low metallicity in Hsyu et al ( 2018) (H18_XMP), as well as those galaxies with EW(Hβ)>100 Å in both Hsyu et al (2018) XMPs (H18_XMP Hβ>100 Å) and the KISS survey (KISS Hβ>100 Å).…”
Section: Number Density Of Eelgsmentioning
confidence: 93%
“…7). To clarify this issue we need a systematic study of the detailed ISM and stellar populations of LAEs across redshift in the style of Izotov et al (2021b) who focused on compact star-forming galaxies.…”
Section: Caveats and Limitationsmentioning
confidence: 99%
“…Sources like Sunburst are unique laboratories to understand the physical mechanisms related to the escaping radiation at cosmological distance. This makes them very informative for the search of ionizing sources at earlier epochs during cosmic reionization (z > 6), when the LyC radiation cannot be observed directly due to high cosmic opacity rapidly increasing in the first 1.5 Gyr (Worseck et al 2014;Romano et al 2019) and are also key for comparison with LyC emitters identified in the local Universe (including candidates), considered analogs of the high redshift ones (Izotov et al 2021a;Schaerer et al 2016;Jaskot et al 2019;Wang et al 2021).…”
Section: Introductionmentioning
confidence: 99%